"It's fun!" using students' voices to understand the impact of school digital technology integration on their well-being. (December 2020) - Mourlam, Daniel James; DeCino, Daniel A.; Newland, Lisa A.; Strouse, Gabrielle A.
Abstract: The purpose of this phenomenological study was to better understand children's perception of their school-based educational technology use and its role in their well-being. Children (N = 23) from the Midwestern U.S. completed an interview and mapping exercise focused on the contexts and factors that impact their well-being, including schools and teachers. Phenomenological analyses of interview transcripts focused on children's perceptions of 1) school educational technology use, and 2) the impact of school educational technology use on their well-being. Children described a variety of school educational technology experiences, which they perceived as having both positive and negative effects on their well-being. Findings are discussed in the context of the historical challenges to school educational technology integration and children's well-being. Highlights: Children describe school technology use and its impact on their well-being. Children have access to technology in school and desire more use during learning. Children believe technology positively impacts their learning and sense of self. Children believe school technology use makes learning fun. Children identify some negative feelings associated with school technology use.